Tổng hợp TiO2 anatase kích thước nanomet bằng phương pháp đốt cháy gel - Đại, Lưu Minh; Nhiệm, Đào Ngọc (Vietnam Journal of Chemistry, 2012)
Titanium dioxide powder has been  synthesised at low temperature (5000C) by the combustion of gel prepared from  polyvinyl alcohol (PVA) and titanium nitrates.Factors affecting on particle sizes of TiO2 such as the PH of solution, temperature of gel formation, mole ratio of concentration of  titanium and  polyvinyl alcohol, temperature of calcinating have been investigated.The nanoparticle TiO2 anatase characterizations were examined by X-ray Diffraction (XRD), Thermogravimetric and Differential Thermal Analysis (TG-DTA), Scanning Electron Microscopy (SEM) and BET ( Brunaure-Emmet-Teller) measurements. Further thermal treatment at 500oC in 2h yields the single phase TiO2 anatase with average primary size < 20 nm. It specific surface area is  50 m2/g for TiO2.